2009
DOI: 10.1039/b907812f
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interaction between skeletal ryanodine receptors in malignant hyperthermia

Abstract: Functional coupling between clustered membrane receptors has been identified as a novel mechanism to improve signaling performance in a number of physiological processes. The potential role of defective inter-receptor coupling in the pathogenesis of disease, however, has not previously been explored. Ryanodine receptors (RyRs), the primary calcium release channel of muscle, usually form ordered two-dimensional arrays in the sarcoplasmic reticulum membranes. Mutations in RyRs are known to cause a number of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Commonly used is a [ 3 H]ryanodine binding assay ( Figure 4C) [19,51,54,60,67,77,79,86,90,92,93,95,96,103,105,108,113,129] As opposed to whole-cell measurements, activities of a single channel can be recorded using planar lipid bilayer electrophysiology ( Figure 4D) [19, 53, 54, 67, 69, 77, 79, 99-101, 105, 107, 108, 111, 112, 114]. Recombinant or endogenous RyR from crude SR vesicle preparations or from purified material are fused into an artificial lipid bilayer formed across two chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Commonly used is a [ 3 H]ryanodine binding assay ( Figure 4C) [19,51,54,60,67,77,79,86,90,92,93,95,96,103,105,108,113,129] As opposed to whole-cell measurements, activities of a single channel can be recorded using planar lipid bilayer electrophysiology ( Figure 4D) [19, 53, 54, 67, 69, 77, 79, 99-101, 105, 107, 108, 111, 112, 114]. Recombinant or endogenous RyR from crude SR vesicle preparations or from purified material are fused into an artificial lipid bilayer formed across two chambers.…”
Section: Methodsmentioning
confidence: 99%
“…We used a well established porcine model of MH in which affected animals are homozygous for the RyR1 R615C mutation (Harrison et al, 1968). When this mutant form of RyR1 (RyR1 R615C ) was compared with the wild type RyR (RyR1 WT ), we found with both PCS and AFM that the purified RyR1 R615C showed significantly reduced oligomerization when compared to RyR1 WT (Liang et al, 2009). AFM observations showed that the number and size of RyR1 R615C clusters formed at a RyR1 concentration of 6 (g protein/mL at the closed state were significantly reduced (Fig.…”
Section: Introductionmentioning
confidence: 99%